CLINICAL COMPARISON OF DIFFERENT METHODS OF POSTERIOR TEETH RESTORATION - Fastovets О.О.; Sardykov Y.А.; Matvieienko, R.Y.; Shtepa V.О. (World of Medicine and Biology, 2024)
Increasing the effectiveness of dental restorations is an important problem in modern dentistry because of the significant prevalence of dental caries. The present research is comparative clinical evaluation of the results of restorative treatment of decayed posterior teeth with direct composite restorations, metal-ceramic and zirconium dioxide onlays. It has been conducted among 90 young aged patients in comparison with a control group, which included 10 healthy persons with intact dentitions. It has been established that the use of zirconium onlays provides the greatest effectiveness of dental restorations according the indicators of their quality, dental status, plaque control, periodontal health, data of computer occlusion diagnostics in the 12-month follow-up period. Further research has to study oral microflora after dental restorations with various materials.